Brood Reduction in Neotropical Birds: Mechanisms, Patterns, and Insights from Studies in the Imperial Shag (Phalacrocorax atriceps) - Svagelj, Walter Sergio
Brood reduction is a within-brood partial mortality due to sibling rivalry and has been observed in a large number of bird species from diverse taxa. Here, I summarize several hypotheses accounting for the adaptive value of brood reduction and discuss different factors that modulate it. A description of different brood reduction systems is made with focus on Neotropical birds. Finally, an integrative approach analyzing brood reduction in Imperial Shags (Phalacrocorax atriceps) is presented to illustrate causes, consequences, and benefits of this breeding strategy. Fil: Svagelj, Walter Sergio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina